Detrital zircon U–Pb ages of Silurian–Devonian sediments from NW Svalbard: a fragment of Avalonia and Laurentia? - Carl H. Pettersson; Victoria Pease; Dirk Frei (2016)
Detrital zircon populations from Silurian–Devonian clastic rocks of NW Svalbard were analysed by U–Pb laser ablation inductively coupled plasma mass spectrometry to investigate the pre-Caledonian provenance of Svalbard's Northwestern Terrane. Changes in the resulting age spectra suggest a major shift in sources from the Laurentian–Avalonian suture in the latest Silurian to the local metasedimentary basement of the Northwestern Terrane in the Late Silurian–Early Devonian, and in the Lochkovian to Grenvillian–Sveconorwegian sources. These data, together with structural, additional geochronological and metamorphic data from Svalbard, East Greenland and Avalonia, support the amalgamation of Svalbard as the result of long-distance transport along sinistral strike-slip faults. A unifying model for the final amalgamation of Svalbard, consistent with the stratigraphical and tectonothermal history of Svalbard, involves fragments from the Grampian orogen and Avalonian crust originally accreted to the Laurentian margin being subsequently transported northward along sinistral strike-slip faults during Scandian deformation.